Micrococcus luteus Teichuronic Acids Activate Human and Murine Monocytic Cells in a CD14- and Toll-Like Receptor 4-Dependent Manner - Yang, Shuhua (American Society for Microbiology, 2001)
Teichuronic acid (TUA), a component of the cell walls of the gram-positive organism Micrococcus luteus (formerly Micrococcus lysodeikticus), induced inflammatory cytokines in C3H/HeN mice but not in lipopolysaccharide (LPS)-resistant C3H/HeJ mice that have a defect in the Toll-like receptor 4 (TLR4) gene, both in vivo and in vitro, similarly to LPS (T. Monodane, Y. Kawabata, S. Yang, S. Hase, and H. Takada, J. Med. Microbiol. 50:4–12, 2001). In this study, we found that purified TUA (p-TUA) induced tumor necrosis factor alpha (TNF-α) in murine monocytic J774.1 cells but not in mutant LR-9 cells expressing membrane CD14 at a lower level than the parent J774.1 cells. The TNF-α-inducing activity of p-TUA in J774.1 cells was completely inhibited by anti-mouse CD14 monoclonal antibody (MAb). p-TUA also induced interleukin-8 (IL-8) in human monocytic THP-1 cells differentiated to macrophage-like cells expressing CD14. Anti-human CD14 MAb, anti-human TLR4 MAb, and synthetic lipid A precursor IV(A), an LPS antagonist, almost completely inhibited the IL-8-inducing ability of p-TUA, as well as LPS, in the differentiated THP-1 cells. Reduced p-TUA did not exhibit any activities in J774.1 or THP-1 cells. These findings strongly suggested that M. luteus TUA activates murine and human monocytic cells in a CD14- and TLR4-dependent manner, similar to LPS.